Contribuição ao conhecimento dos Clytini neotropicais (Coleoptera, Cerambycidae, Cerambycinae) Contributions to the knowledge of the Neotropical Clytini (Coleoptera, Cerambycidae, Cerambycinae) - Maria Helena M. Galileo; Ubirajara R. Martins (Revista Brasileira de Entomologia, 2007)
São descritos e figurados os novos táxons da Colômbia (Magdalena): Cetimaju, gen. nov., espécie-tipo C. abare sp. nov. e Tanyochraethes minca sp. nov.; do Brasil: M. ycoca sp. nov. (Amazonas) e Neoclytus turuna sp. nov. (Amazonas, Pará); do Equador: N. anama sp. nov. (Loja); do Peru: N. potiuna sp. nov. (Cuzco); do Peru e da Bolívia: N. pinima (Ica, Chaparé). The following new taxa are described and figured: from Colombia (Magdalena): Cetimaju, gen. nov., type species C. abare sp. nov. and Tanyochraethes minca sp. nov.; from Brazil: M. ycoca sp. nov. (Amazonas) and Neoclytus turuna sp. nov. (Amazonas, Pará); from Ecuador: N. anama sp. nov. (Loja); from Peru: N. potiuna sp. nov. (Cuzco); from Peru and Bolívia: N. pinima (Ica, Chaparé).